(untitled) (Research, Society and Development, 2024)
Duloxetine, a serotonin-norepinephrine reuptake inhibitor (SNRI), has established itself as a versatile therapeutic agent across a spectrum of psychiatric and neurological disorders. The objective of this article is to update the pharmacological properties of duloxetine. To this end, a review was carried out on the pharmacology, clinical efficacy, safety and tolerability of duloxetine, focusing on its application in the treatment of major depressive disorder (MDD), generalized anxiety disorder (GAD), diabetic peripheral neuropathic pain, fibromyalgia and musculoskeletal pain. chronic. Comparative analyzes highlight the relative effectiveness of duloxetine versus other antidepressants and its unique advantage in managing conditions with overlapping mood and pain symptoms. Safety profiles and pharmacological interactions, particularly with NSAIDs and tamoxifen, highlight the importance of personalized treatment plans and vigilant monitoring. The review concludes with an assessment of the clinical utility of duloxetine, emphasizing individual patient assessment to maximize therapeutic outcomes while minimizing risks. Future research directions are suggested to further delineate the role of duloxetine in treatment algorithms and explore potential new indications.